Human Health and Environmental Hazards Associated with Plastic Waste: A Review and Spatial Mapping in Informal Settlements of Kampala, Uganda - Mensah, Elijah. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Justin Hollander, and Julian Agyeman.; Committee: Justin Hollander, and Julian Agyeman.; Keywords: Urban planning, Environmental justice, and Environmental studies.